Urgensi Masalah Lingkungan Hidup sebagai Materi Siaran Televisi Daerah - Surianor . (UIN Antasari Banjarmasin, 2017)
Environmental issues have become universal and international issues. Indonesia can not leaving the hands of this problem because in many areas of severe environmental damage, either by the action of deforestation, logging, mining, industrialization, construction of residential, shopping and so on are not paying attention to the safety and preservation of an environmentally build awareness of all parties the importance of maintaining and save the environment takes an active role of the mass media, especially television. Television media in areas where environmental damage occurs should be much more proactive broadcast environmental damage. If there needs to be a regular event materials specifically preach condition and damage.